398 QUANTITATIVE CHANGES IN DIAGNOSTIC CRITERIA OF METABOLIC SYNDROME IN OVERWEIGHT CHILDREN AND ADOLESCENTS ENROLLED IN A 12-WEEK MEDICALLY SUPERVISED RISK FACTOR REDUCTION PROGRAM. (1st January 2006) - Luna, C. F.; Evans, W. N.; Mayman, G. A.; Acherman, R. J.; Kip, K. T.; Cass, K. A.; Rothman, A.; Gustafson, A.; Lowe, A.; Coviello, L.; Restrepo, H.
Abstract : Background: Metabolic syndrome (MS) occurs in 29% of obese children. MS in adults is a risk factor for diabetes and cardiovascular disease. Although long-term consequences MS in childhood are unknown, early intervention with programs aimed to modify lifestyle patterns may have a positive effect on different parameters used to diagnose MS. Objective: To assess the effect of a 12-week medically supervised program of nutritional counseling and exercise on each diagnostic criterion of MS in a group of overweight children. Methods: Data from the 265 children with BMI ≥ 95th percentile enrolled in the program was analyzed. MS criteria were defined following NHANES III guidelines. The change in the mean value at 12 weeks for each positive criterion of MS found at entry was analyzed using paired t -test. Results: There were 124 girls and 141 boys, mean age: 11.4 years (range: 6-18 years), mean BMI Z-score: 2.34 ± 0.34, Hispanic: 48%, Caucasian: 32%, African American: 13%, and other races: 7%. Changes in mean values of each MS criterion are shown in the table below. Conclusion: A 12-week intervention program aimed to modify nutritional and exercise patterns in this group of overweight children and adolescents was associated with significant improvement in the mean values of triglycerides, HDL cholesterol levels, and systolic blood pressure percentile, when these values were initially abnormal according to the definition of MS.